Development of Cyberblog Learning Media to Improve Logical Thinking Concepts on Computer Science Students. - Wahyudin; Abdulhak, Ishak; Munir; Wahyudin, Dinn (Pertanika Journal of Social Sciences & Humanities)
The aim of this study is to improve the mastery of the concept of student's logical thinking, especially in learning algorithm, applied to a new learning model. It is named the "cyberblog" model, which is a web-based learning model that combines web and blog functions in one weblog concept in the form of text, audio and video developed with sources from the internet and researchers themselves. Therefore, this research proposes the Cyberblog model and describes its implementation. Some experiments on the concept of logical thinking are conducted. The sample of this study is students of the Department of Computer Science in Bandung city. Data were collected by using a test mastery of the concept of logical thinking and field notes and will grow to a computer network-based media (internet) specialized in the learning algorithm that is considered difficult. The results showed a medium of learning that can improve student's logical thinking skills.